2018
DOI: 10.1177/1363461518794218
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Meaning in Life Questionnaire – Hausa version among internally displaced persons in Nigeria

Abstract: Valid measurement of meaning in life (MIL) is crucial for cross-cultural understanding of the construct. The Meaning in Life Questionnaire (MLQ), a widely used measure of MIL, has yet to be translated into any indigenous African language. The current study presents a preliminary report of a Hausa language translation of the MLQ, the MLQ-Hausa version (MLQ-H), and its reliability and validity in a Nigerian sample. Participants were 809 internally displaced persons (IDPs) (50.7% males) in Kabusa IDP Centre in Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 43 publications
5
25
2
Order By: Relevance
“…is finding is consistent with the results of some studies [1,33] and contradicts some others that have reported a significant correlation between the MLQ and sociodemographic variables [23].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…is finding is consistent with the results of some studies [1,33] and contradicts some others that have reported a significant correlation between the MLQ and sociodemographic variables [23].…”
Section: Discussionsupporting
confidence: 91%
“…As for the question of whether or not the MLQ has construct validity, a confirmatory factor analysis was conducted to explore its factor structure and construct validity. CFA supported the two-factor model, including the Presence of Meaning and Search for Meaning subscales, consistent with the results of several previous studies [1,[29][30][31][32][33][34]40]. e results also showed that item 9 ("My life has no clear purpose"), which is the only reversed item in the MLQ-P, had a significantly lower factor loading (P < 0.05) onto the other items on this subscale (MLQ-P � 0.18, MLQ-S � 0.44) and seems to be a problematic item.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations